2015
DOI: 10.1021/ie5029649
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of an Organic Thin-Film Solar Cell of PTB7:PC71BM with an Alcohol-Soluble Polyelectrolyte Interlayer Prepared Using the Spray-Coating Method

Abstract: We report the effect of a poly[(9,9-bis(3′-(N,N-dimethylamino)propyl)-2,7-fluorene)-alt-2,7-(9,9-dioctyl fluorene)] (PFN) interlayer on the performance of PTB7:PC 71 BM-based organic thin-film solar cells (OTFSCs) prepared using the spray-coating method. The active layer shows a broad absorption, but the effective contact area in the bulk hetrojunction (BHJ) is small because of the formation of aggregates on the surface. The surface aggregates dissolved by the addition of 1,8-diiodooctane (DIO) to the PTB7:PC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…PEDOT only showed a bad PCE of 2.91% with a FF of 48.04%. The same devices (ITO/HEL/PTB7:PC71BM/Al) with PEDOT:PSS modified anode showed a J SC of 12.77, V OC of 0.72 and PCE of 4.28% with a FF of 46.40% as shown in reference 46 . The PCE of It encourages us to study its potential further in future.…”
Section: Dispersion Of Pedot and Its Application In Polymer Solar Cellsmentioning
confidence: 63%
“…PEDOT only showed a bad PCE of 2.91% with a FF of 48.04%. The same devices (ITO/HEL/PTB7:PC71BM/Al) with PEDOT:PSS modified anode showed a J SC of 12.77, V OC of 0.72 and PCE of 4.28% with a FF of 46.40% as shown in reference 46 . The PCE of It encourages us to study its potential further in future.…”
Section: Dispersion Of Pedot and Its Application In Polymer Solar Cellsmentioning
confidence: 63%
“…Such information is critically important in developing solar cell materials based on water or organic solvent-soluble polyfluorenes 21 and on solid-phase polyfluorenes. 33 Here, we report PET dynamics in non-covalent associations of cationic polyfluorene, namely poly[(9,9-di(3,3'-N,N'-trimethyl-ammonium) propyl fluorenyl-2,7-diyl)-alt-co-(9,9-dioctylfluorenyl-2,7-diyl)] diiodide salt (PFN) with neutral electron acceptor 1,4-dicyanobenzene (DCB). We carefully chose DCB as an electron acceptor because of its unique optical properties including the absence of a spectral overlap with the donor to rule out the possibility of energy transfer process rat.…”
Section: Introductionmentioning
confidence: 99%
“…When the o-DCB volume content ratio exceeds 60 vol.%, J SC and PCE are both decreased to 13.7 mA/cm 2 16.1 mA/cm 2 and 63.1%, respectively, resulting in the PCE of 7.62% accordingly. The performance of our AS coated device in air ambient is as high as the OSCs based on PTB7:PC 71 BM using conventional spin coated method in nitrogen ambient [41], and to the best our known, it is the highest performance using AS coating method [29]. Then, when the ratio of o-Xy is more than 20 vol.%, the device performance of OSC will gradually decrease.…”
Section: Detail Analysis Of the Device Performancementioning
confidence: 71%
“…Numerous physical properties of the solution, such as the surface tension (ST), volatility and wettability, directly affect the AS processes of atomization, flying and deposition [27,28]. For instance, the photovoltaic performances of OSCs based on PTB7:PC 71 BM BHJ system with high PCEs up to 7-9% from spin coating method decrease to the PCE of 5-6% when using AS coating method [29,30]. It is found that the conventional BHJ system only with a single solvent and additive cannot perfectly match with the AS coating method due to the simplex physical property of solution, which usually results in large aggregation domains as well.…”
Section: Introductionmentioning
confidence: 99%